MTA and calcium hydroxide for pulp capping MTA e hidróxido de cálcio para proteção pulpar direta - Alexandra Mussolino de Queiroz; Sada Assed; Mario Roberto Leonardo; Paulo Nelson-Filho; Léa Assed Bezerra da Silva (University of São Paulo, 2005)
This study evaluated the biocompatibility of mineral trioxide aggregate (MTA) after direct capping of exposed pulp tissue in dog's teeth. Class I cavities were prepared in 26 teeth from 3 adult dogs. MTA was applied over the exposed pulp in 13 teeth and paste of calcium hydroxide plus distilled water (control) was applied in the remaining 13 teeth. After 90 days, the animals were killed; the maxilla and mandible were dissected and sectioned to obtain individual roots. The samples were processed histologically. The pulp and periapical response observed with the use of MTA was similar to that of calcium hydroxide paste. In all specimens, there was a dentin bridge obliterating the exposure, an intact odontoblastic layer, no inflammatory cells, normal connective pulp tissue, normal apical and periapical regions and no bone tissue changes. Similar to calcium hydroxide, MTA presented excellent response when used for direct pulp capping. O objetivo deste trabalho foi avaliar a biocompatibilidade do agregado de trióxido mineral (MTA), após proteção pulpar direta em dentes de cães. Foram preparadas cavidades de Classe I, em 26 dentes de 3 cães adultos. O MTA foi aplicado sobre 13 dentes e a pasta de hidróxido de cálcio (grupo controle) foi aplicada sobre os 13 dentes remanescentes. Após 90 dias, os animais foram mortos, a maxila e a mandíbula foram dissecadas e os dentes foram seccionados para obtenção de raízes individualizadas. Os espécimes foram processados histologicamente. A resposta do tecido pulpar e periapical foi semelhante para o MTA e o hidróxido de cálcio. Em todos os espécimes havia ponte de dentina obliterando o local da exposição pulpar, camada odontoblástica íntegra, ausência de células inflamatórias, tecido pulpar normal, e ausência de alterações na região periapical e óssea. Da mesma maneira que o hidróxido de cálcio, o MTA apresentou excelente biocompatibilidade quando usado para proteção pulpar direta.